Life Satisfaction as Mediator Between Social Integration and Parental Perception in Schizophrenia and Bipolar Disorder: Implications for Social Work Intervention - Sahin, Ayse Bedia; Bayram, Yunus; Artan, Taner; Bayram, Yunus (Routledge Journals, Taylor & Francis Ltd, 2025)
The present study examines relationships between social integration, life satisfaction, and perception of being a parent among individuals with schizophrenia or bipolar disorder, investigating life satisfaction's mediating role between social integration and perception of being a parent. The research is grounded in ecological systems theory. Using structural equation modeling and group comparisons, the research analyzed data from 382 outpatients (schizophrenia: n = 216; bipolar disorder: n = 166) receiving services in Community Mental Health Centers in Istanbul, T & uuml;rkiye. Results demonstrate that social integration significantly and positively predicts both life satisfaction and perception of being a parent. Moreover, life satisfaction positively predicts perception of being a parent, partially mediating the relationship between social integration and parental role perception. Although individuals with bipolar disorder reported higher levels of social integration and life satisfaction than those with schizophrenia, no significant differences were found in perception of being a parent, and the mediational pathway remained consistent across both diagnostic groups. These findings contribute to the limited literature on parenthood experiences among individuals with serious mental illness by applying an ecological framework to this marginalized population. Future research should employ longitudinal designs and explore culturally diverse contexts to further clarify these relationships and strengthen implications for social work interventions.
Keywords: Social Integration; Perception Of Being A Parent; Life Satisfaction; Schizophrenia; Bipolar Disorder; Social Work Intervention